2011
DOI: 10.1158/1055-9965.epi-11-0515
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mortality in Women with Breast Cancer Detected during Pregnancy and Different Periods Postpartum

Abstract: Background: Because of a continued trend toward postponed childbearing, the incidence of pregnancyassociated breast cancer (PABC) is likely to increase. This study investigated the mortality in women with PABC in relation to when the tumor was detected (during pregnancy, different postpartum periods) and by time since diagnosis, compared with women with non-PABC.Methods: A population-based cohort study of 15,721 Swedish women diagnosed with breast cancer between ages 15 to 44 years, of whom 1,110 (7%) had a PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
115
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 27 publications
10
115
1
2
Order By: Relevance
“…Further, we observed an increase in tumor-associated lymphatics in a cohort of postpartum breast cancers, which correlates with increased lymphatic vessel invasion. These results suggest that physiologically normal lymphangiogenesis that occurs in the postpartum involuting breast may facilitate breast cancer dissemination in postpartum women, an observation that may explain the increased lymph node metastasis in our postpartum patient population as well as the published increased risk for metastatic disease observed in this patient population (8)(9)(10).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Further, we observed an increase in tumor-associated lymphatics in a cohort of postpartum breast cancers, which correlates with increased lymphatic vessel invasion. These results suggest that physiologically normal lymphangiogenesis that occurs in the postpartum involuting breast may facilitate breast cancer dissemination in postpartum women, an observation that may explain the increased lymph node metastasis in our postpartum patient population as well as the published increased risk for metastatic disease observed in this patient population (8)(9)(10).…”
Section: Discussionmentioning
confidence: 58%
“…In murine breast cancer models, postpartum mammary gland involution promotes mammary tumor growth, invasion, and metastasis (1,3,7). Consistent with these preclinical data, women diagnosed after childbirth and up to 5 years postpartum, cases we and others define as postpartum breast cancer (2), have increased risk for metastasis compared with age-matched nulliparous patients with similar stage disease (8)(9)(10). However the mechanism of increased metastasis in postpartum patients remains unknown.…”
Section: Introductionmentioning
confidence: 61%
“…As far as outcome of PABC is concerned data are conflicting: some authors showed no difference in outcome of PABC and non-PABC cases [14,16,24], while others consider PABC as having unfavorable prognosis [1,[7][8][9]. In a recent metaanalysis of 30 studies, Azim et al found that PABC patients had poor overall survival especially if breast cancer was diagnosed within 1 year postpartum [25].…”
Section: Discussionmentioning
confidence: 99%
“…The definition is not unanimous however, some authors define the postpartum time frame from 6 months to 2 years after delivery [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation